Pemanfaatan Daun Salam, Batang Serai dan Buah Pepaya Sebagai Inovasi Dalam Produk Makanan Sehat dan Potensi Dalam Pengembangan UMKM di Desa Sungai Pinang - Aliyya Intan Misyilla; Debi Setiawan; Amelia Putri; Aprilia Asri; Nantika Indah Sari; Ridha Ramana; Yurnaliza; Yusman; Indriani; Cheesa Priscilla Ronald; Mahendra Kurniawan Manurung; Bella Patricia; Shanty; Seny Mahara (Yayasan Rahmatan Fidunya Wal Akhirah, 2023)
Sungai Pinang is one of the villages located in Tambang District, Kampar Regency. Sungai Pinang Village has 4 hamlets with each consisting of 2 RWs and 4 RTs. This activity is located in Hamlet III, RT 02, RW 01. Activities carried out include making 7 superior products consisting of Bay Leaf Herbal Tea; Bay leaf capsules; Spray, Serum, Lemongrass Oil Diffuser; Papaya Jam and Pudding which were then socialized to Posyandu mothers and residents around Sungai Pinang Village. This activity is carried out to develop knowledge and skills, as well as educate the public to be able to utilize natural ingredients as a source of food and medicine.